ORGANIZATIONAL AND ECONOMIC MECHANISM FOR IMPROVING THE QUALITY OF HUMAN RESOURCES OF THE REGION - E. A. Ostapenko (Вестник университета, 2021)
The quality of human resources, considered as a set of certain assessment criteria that are dynamic in nature, due to the basic indicators and factors of the internal and external environment of the social and economic system of the region needs a comprehensive management impact aimed at improving the system and its elements. The quality of human resources in socio-economic systems, as well as tools aimed at the formation of qualitative parameters, form the problem of improving the economic mechanism for improving the quality of human resources in modern conditions, which should take into account the management goals, the state and prospects for the development of quality parameters of the system elements, to ensure the effective functioning of the conceptual model of quality management of human resources.